Etude du comportement mecanique pour Ia conception des structures textiles: Application aux bandes transporteuses - Chaffoui, Hassan; Play, Daniel (European Journal of Computational Mechanics, 1998)
The conveyor belts that transport raw materials, must support a high and sufficiently varying tensiles constraints. Increase in strangth characteristics implies a good knowledge of the role of constituants. A solid woven is impregnated by resin. The homogenization theory has been used to define more and more complex models has allowed the analysis of different kind of industriel problems. This, a symetric plate model is derived using sub domain assembling, an assymetric plate model to consider the continuity and undulation of fibers in fabric composite. Finally, a three-dimensional homogenization model enables us to locate different level of models under study. Element based on different models are assembled in a finite element computer program. In this paper, only, the assymetric plate model is presented in detail.